Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Literasi Sains Peserta Didik Kelas V - Ulfiani Ulfiani; Erma Suryani Sahabuddin; Sayidiman Sayidiman (STKIP Andi Matappa Pangkep, 2023)
This research aims to determine the effect of the Project Based Learning (PjBL) learning model on students' scientific literacy abilities at UPT SPF SDN Mamajang I Makassar City. The research design used was Nonequivalent Control Group Design. The independent variable in this research is the Project Based Learning learning model while the dependent variable is the students' scientific literacy abilities. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. Data was collected from the pretest, treatment and posttest divisions. The treatment provided is in the form of a project to make a simple water filter device. This research shows that the Project Based Learning (PjBL) learning model on students' scientific literacy abilities is in the very effective category. After hypothesis testing and analysis were carried out, the results obtained show that there is a significant influence of the Project Based Learning (PjBL) learning model on participants' scientific literacy abilities. educate. The conclusion in this research is that the application of the Project Based Learning (PjBL) learning model has an effect on the scientific literacy abilities of class V students at UPT SPF SDN Mamajang I Makassar City.